Spatial Disorientation Simulator - Bogusz Dariusz (Safety & Defense, 2018)
The article describes the characteristics of the spatial disorientation simulator constructed for the Polish Air Force Academy aviation training. Using the spatial disorientation simulator enables safe training for military pilots, as it simulates visual illusions and spatial disorientation. The simulator makes it possible to train pilots in spatial disorientation conditions for every possible type of aircraft, through designing and conducting the proper aircraft cabin models. Spatial disorientation training has to main aims. The first one is familiarizing the pilots with spatial disorientation phenomenon, and providing them with essential knowledge and abilities through theoretical and practical acquaintance with physiological limitations. Such limitations are related to the impact of different aviation environmental aspects on the human body. The second aim of the training is increasing the efficiency of aviation training, in relation to recognizing, analyzing and proper reacting to real and simulated occurrences, which lead to spatial disorientation. The author describes main stages of the training conducted during the spatial disorientation course. The article categorizes major features of different spatial confusion types and characterizes types of air illusions.